2022
DOI: 10.1029/2021ms002715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonseasonal River Discharge on Sea Surface Salinity and Height

Abstract: River discharge into the ocean influences a range of ocean properties and processes, such as salinity, ocean dynamics, marine biology and ecosystems, and biogeochemistry (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…For example, Piecuch et al (2018) suggested that the rive discharge is significantly correlated to sea-level changes on the United States Atlantic and Gulf coasts. Chandanpurkar et al (2022) predicted nonseasonal river-discharge impact on sea level variability using the simplified theory proposed by Piecuch et al (2018). Similarly, precipitation and buoyancy forcings could also play roles in the variations of coastal sea level (Lee et al, 2019;Wang et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Piecuch et al (2018) suggested that the rive discharge is significantly correlated to sea-level changes on the United States Atlantic and Gulf coasts. Chandanpurkar et al (2022) predicted nonseasonal river-discharge impact on sea level variability using the simplified theory proposed by Piecuch et al (2018). Similarly, precipitation and buoyancy forcings could also play roles in the variations of coastal sea level (Lee et al, 2019;Wang et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Chandanpurkar et al. (2022) predicted nonseasonal river‐discharge impact on sea level variability using the simplified theory proposed by Piecuch et al. (2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Deep-learning networks have been widely used in oceanography due to the strong feature extraction capability. At present, it is difficult to obtain ocean observation data and the data sources are scarce, which has an impact on the performance of assimilation [14,23,24]. The characteristics of satellite observation data in a large range can effectively expand ocean observation data, but satellite observation can only obtain ocean surface information, and it is difficult to provide deep ocean information for assimilation algorithms [25].…”
Section: Methodsmentioning
confidence: 99%
“…ESTAR, STARRS, SMOS, Aquarius and SMAP). More detailed information on this is given in [20] [21], and references therein. Another interesting aspect is the combination of sea surface salinity from these sensors and sea surface height from satellite altimetry [21] but this is out of the scope of our work.…”
Section: Introductionmentioning
confidence: 99%